The ConceptofThird Space inthe Buddha of Suburbiaby Hanif Kureishi1991 - BELAHCENE ,AOUALI; GUELLIL,Assia (Faculty of Letters and Foreign Languages Department of English, 2017)
Black British Literature is the literature written in English by Caribbean, Asian, African and other people who originate from the former British Empire. This project tends to investigate the chaotic situation of the minorities living in the metropolitian city of London, examining the effects of changing places and mobility on the process of “space production” taking into consideration shifts from periphery to the centre. This present work is divided into three chapters; the first chapter is about the theoretical background about colonialism. The second chapter will give an overview concerning the emergence of Black British Literature and issues of hybridity and third space. The last chapter tends to highlight the theories used in this novel. Hanif Kureishi’s portrays hybrid characters that are seeking a sense of belonging. The struggle of these characters to find their own spaces in the post-imperial London is studied according to Henry Lefebvre theories of “Production of Space” as well as Soja and Bhabha’s “Third Space” to illustrate the possibility of the existence of produced third space where all these characters express and celebrate their hybrid identities